Laser Interstitial Thermal Therapy for Cavernous Malformations: A Systematic Review - Yousefi, MD, Omid; Sabahi, MD.MPH, Mohammadmahdi; Malcolm, MD, PhD, James; Adada, MD, Badih; Borghei-Razavi, MD, Hamid (Frontiers in Surgery, 2022)
Background: Microsurgical resection of intracranial cavernous malformations (CM) is regarded as the standard treatment, but in recent years, there has been a trend toward minimally invasive procedures like ablation of such lesions by using laser interstitial thermal therapy (LITT). Methods: A systematic search using keywords “laser interstitial thermal therapy” OR “LITT” AND “cavernoma” OR “cavernous angiomas” OR “cavernous malformations” was conducted in MEDLINE (PubMed), Scopus, Embase, and Cochrane electronic bibliographic databases and studies reporting the outcome of LITT procedure on intracranial CM were included. The demographic data, symptoms of patients, location and size of the lesion, and surgical outcome were extracted from the articles. Result: Six studies, reporting the outcome of 33 patients were included in this review. In 26 patients, CM was identified as the epileptogenic foci and in others, CM was the source of headache or focal neurological deficits. LITT led to a satisfactory outcome in all patients except for three who achieved improvement in symptoms after the open resection of the lesion. Most of the post-operative complications were transient and resolved at the time of the last follow up. Cyst formation at the previous ablated CM site was reported as the long-term complication of LITT in one case. Conclusion: LITT can provide a comparable outcome to the open resection of CMs, by having less invasiveness, even in deep and eloquent area lesions, and complications that are often temporary and disappear gradually. However, technical issues, such as thermal monitoring during the procedure, are considered a challenge for this procedure in CMs. Further studies with a larger population are needed to report this method's long-term outcome and complications on CMs.